Complicated magnetic foreign objects of the gastrointestinal tract: two clinical cases - Dmitrii V. Shchegolev; Dilyaver A. Chalbash; Memet Yu. Umerov (LLC "MEDIAFORMAT", 2024)
Among the foreign bodies (FB) of the digestive tract, magnets account for approximately 1.97%. The presence of magnetic FB in the gastrointestinal tract is characterized by nonspecific symptoms, difficulties in collecting anamnesis due to the age of patients and low alertness of parents and medical professionals. Currently, multiple magnets are the most dangerous FB of the gastrointestinal tract. Being in different parts of the digestive tract, they are attracted to each other and cause a number of complications: ischemia and bedsores of the wall of the hollow organ, volvulus, intestinal obstruction, perforation of the wall and surrounding anatomical structures, intestinal fistulas, bleeding, intussusception. 2 clinical examples of the presence, developed complications and surgical removal of multiple magnetic FB and postoperative management of patients are described. The peculiarities of the cases are the formation of an interintestinal fistula passing through the mesentery of the small intestine, as a result of the attraction of magnets located in different parts of the small intestine, and the formation of 4 perforations located in different parts of the intestine, as a result of the attraction of 3 magnets. Magnetic FB themselves in the gastrointestinal tract, as a rule, do not have clinical manifestations; symptoms correspond to developed complications. Not all children report ingesting magnetic FB. To exclude magnetic FB left during surgery in the gastrointestinal tract, intraoperative radiography is necessary.